The impact of an introduction to community psychology course on refugee sense of empowerment - Acree, Kamauria (AUC Knowledge Fountain, 2018)
This study examines the impact of an Introduction to Community Psychology course on the empowerment of adult refugees living in Egypt. The course was designed and implemented at a refugee center located in downtown Cairo. For a period of 10 weeks, refugees enrolled in the course conducted a community needs assessment (CNA) to identify the resources and needs of a community in Cairo. The refugee students then designed and implemented a community intervention to help meet the needs of their chosen community. The course sought to empower adult refugees by 1) increasing their knowledge and skill level of the CNA process, 2) building their knowledge of community intervention skills, 3) imparting to them practical and applicable skills in working with communities and groups, 4) giving them the opportunity to effect change in their own communities, and 5) providing them with an opportunity to build relationships across refugee communities. To assess the impact of the course, students completed pretest and posttest scales measuring optimism, self-esteem and self-efficacy along with a retrospective survey assessing learning. Reflective journals kept by students during the course were also analyzed for themes related to learning and empowerment. Results revealed that, overall, the Introduction to Community Psychology course had a meaningful impact on students learning experience but did not significantly impact levels of optimism, self-esteem or self-efficacy. Sixty percent of participants reported a large increase in their knowledge of the steps of conducting a CNA. In addition, a thematic analysis identified four key themes: (a) improved understanding of how to conduct a CNA, (b) key content knowledge of the field of community psychology, (c) empowering learning environment, and (d) greater understanding of how to plan and design a community intervention. The results provide insight into the strengths and challenges of using a community psychology approach to empower refugees.